Impact of climate on tourist demand - Wietze Lise; Richard S. J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2001)
Tourism, being volatile and situation-specific, is responsive to climate change. A cross-section analysis is conducted on destinations of OECD tourists and a factor and regression analysis on holiday activities of Dutch tourists, to find optimal temperatures at travel destination for different tourists and different tourist activities. Globally, OECD tourists prefer a temperature of 21C (average of the hottest month of the year) at their choice of holiday destination. This indicates that, under a scenario of gradual warming, tourists would spend their holidays in different places than they currently do. The factor and regression analysis suggests that preferences for climates at tourist destinations differ among age and income groups.
Keywords: D12; R19; Q26; 330; Tourist demand; climate change; factor analysis; regression analysis; cross-section analysis; Klimawandel; Internationaler Tourismus; Nachfrage; OECD-Staaten